KOHESI DAN KOHERENSI WACANA PADA SKRIPSI MAHASISWA ANGKATAN 2008 PRODI PBSI UNIPA SURABAYA - Sri Budi Astuti; Bahauddin Azmi; Indayani Indayani (WAHANA, 2013)
This study’s purpose is to describe the cohesion and coherence on scription of the students study program PBSI Unipa Surabaya. The phenomenon is studied because scription is a form of written apparatus which has grammatical tendency, more subordinative arrangement, the use of connecting tools, long thing phrases, and havaing subject predicate phrases, and having subject predicate structures. The data of the thesis are in the forms of cohesion and coherenceof students 2008 scription, study program PBSI Unipa Surabaya in seven scriptions.The documentation collecting data technique is use, they are identification, classification base on cohesion and coherence parts, and data coding. Data analyses technique in this study use descriptive qualitative technique. The result of data collecting which is deleted to cohesion and coherence in the students script 2008 study program PBSI Unipa Surabaya.Cohesion’s mark of inter sentences of studens 2008 descourse study program PBSI Unipa Surabaya. Inter sentences descourse sign of the students 2008 PBSI includes: grammatical aspects (pronomina, subsitution, conjunction, and elipsis): lexical aspects (hyponym, repwtition, and colocation). Coherence includes: signed coherence sign of meaning sign’s, adictive, alternative, turn, and stress); complete meaning’s and coherence without signs.